Adjustment to higher education among students with mental health disorders. Issue 1 (2nd January 2023) - Zorach, Inbar Aharoni; Lipka, Orly
ABSTRACT : The current study examined the adjustment to higher education among students with mental health disorders, focusing on adjustment to post-secondary education, emotional and metacognitive variables. The participants were 123 students who had already completed at least one year at an institution of higher education: 63 students who self-identified themselves with mental health disorders and 60 students who did not identify with any mental health disorders or disability. Students with mental health disorders reported on lower levels of adjustment (social, emotional, institutional, and academic) to post-secondary education than students with no mental health disorders. In addition, students with mental health disorders reported lower satisfaction with life, academic self-efficacy, and higher levels of test anxiety than students without mental health disorders. Furthermore, significant between-group differences were found in three meta-cognition subscales. Lastly, satisfaction with life, test anxiety, academic self-efficacy, and disability status and five metacognition subscales predicted 75% of the variability in adjustment to higher education in the entire sample. These findings suggest that following their first year in higher education, students with mental health disorders continue to experience difficulties in social, emotional, institutional, and academic adjustment. Implications of the results are discussed.